ECONOMIC GEOGRAPHICAL CHARACTERISTICS OF THE DEVELOPMENT OF INDUSTRIAL NETWORKS OF KASHADARYA REGION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article describes the potential of Kashkadarya region, which has a special place in the development of economic sectors of the Republic of Uzbekistan, and the territorial organization of industrial sectors.